Inhibitory Activity of Ogi on Salmon ella typhi (Biological Sciences - PJSIR, 2007)
Th e su r v i va l of two str ai n s of Salmonella typhi , ATCC 1 4028 and SSH 4 1 , were invest igated i n on e u n cooked and two cook ed (one ma i nta i n ed at ?: 25 °C, and second mai n t a i n ed at :: 35 °C) samp l es of Ogi , a ferm en ted cerea l porridge. Ogi was obtai n ed by fc1111en tation of maize for five d ays. Th e foods w ere i n ocu l a ted with a k n own con cen t rat i on of t h e cel l su spensi on of th e te t organ i sm s w h i ch ·h ow ed a sh arp decrea e i n th ei r n u mbers a fter 5 h . Th e anti bacter i a l effect of un cook ed Ogi w as m ore pron ou n ced on t:h e two strai n s of Salmonella typ hi ATCC 14028 an d Salmonella typ hiSH 4 1 , w ith 4 .57 x I oi c.fu / h a nd 2.20 x I 03 cfu /h decl i n e i n grow t h ra te respectively w i th i n 5 h . Stap hy lococcu  sp ,A p ergillus sp. , Fusarium. sp., Ep holosp orwn sp., Pediococcus sp., l uconostoc sp ., La ctobaci/ / us sp., Cory nebacterium sp., Saccharomyces cerevisiae, Alk aligenes sp., and Candida mycoderma were isol ated from th e fresh an d ferm en ted maize at d i fferent times of fermentati on . It i s i nteresti ng to n ote th a t t he fem1enti n g organi sms depend ed mu ch on calci u m (67%) and  sodiu m  (30%) for th ei r grow th .